The affair of the necklace [videorecording (DVD)] - Newman, David, 1954- (Warner Home Video, 2002)
In pre-Revolutionary France, a young aristocratic woman left penniless by the political unrest in the country, must avenge her family's fall from grace by scheming to steal a priceless necklace.